STATUS OF WOMEN’S EDUCATION AND ITS IMPORTANCE (International Journal of Food and Nutritional Sciences, 2022)
The right to education or the right to education is illiteracy, respect for human rights of young people and fundamental freedoms and efforts to eradicate discrimination in education, with the United Nations, United Nations organization for educational, scientific and cultural development. It is proceeding with unity and cooperation. The United Nations recognized the year 1970 as the international year of education and established the United Nations educational, scientific and cultural development corporation. The right to education mentioned in the universal declaration of human rights the international covenant one economic, social and cultural rights the international convention on the elimination of all forms of discrimination against woman the convention on the elimination of all forms of discrimination against woman and the convention on the rights of the child. The universal declaration of human rights state as that everyone should enjoy the right to education. Article26 of the universal declaration of human rights states that everyone has the right to education. A country or a nation can be advanced politically, socially, culturally and economically by having access to education. Education of women is far more important than men. According to Mahatma Gandhi, men’s education is the education of an individual but women’s education is the education of the whole family. Unless women have an opportunity to have the right to education, a nation cannot advance and achieve its goal. The female education has been the key to the progress of every nation. While underlying the importance of women’s education, Jawaharlal Nehru, said, “Education of boys is education of one person, but the education of a girl is the education of the entire family”. Long before the government took up the cause of women’s education, the missionaries were already at work. They came to India mainly to spread Christianity. They selected education as a tool to carry on their missionary work. They made much effort for women’s education in madras presidency. Gradually, their work in the field of female education was also increased. Till the advent of European missionaries, every village in Tamil Nadu had a pial school, popularly known as tinnai pallikudam. Thus, higher education was extended to all levels of students, irrespective of caste, creed and colour. With the arrival of the protestant danes at tranquebar on the on the south east coast in 1706, began. This paper to know the position of women education, Equality of education, Women’s Rights to education.